(untitled) (Global Journals of Research in Engineering, 2016)
Recent years have witnessed extensive research efforts that aim at improving the aerodynamic performance of aircraft. while most of the efforts are drawn towards high-lift systems, simple and innovative designs like Gurney flaps, trapped vortex cavities and backwardfacing steps can have a significant effect on enhancing the aerodynamic properties of airfoils. One of those simple ideas is the Kline-Fogleman modified airfoil (KFm-2), which is basically an airfoil with a backward-facing step on the upper surface located at midway the chord length. it is claimed that the step creates a low pressure recirculation region on the suction side of the airfoil that may enhance the lifting force. This study will numerically examine the ability of the KFm-2 design to enhance the lift and drag properties of a NACA 2412 at a high Reynolds number of 5.9 #xD7; 106. The effect of the step depth and the step angle will be thoroughly examined.